Korelasi Kadar Feritin dan ALT pada Pasien Talasemia Beta Mayor: Tinjauan Pustaka - Mutiara Maharani; Intanri Kurniati; Muhammad Maulana; Susianti (CV. Jasa Sukses Abadi, 2025)
Beta thalassemia major is an autosomal recessive genetic blood disorder caused by mutations in the globin gene, resulting in impaired globin chain synthesis. It represents the most severe form of thalassemia and is characterized by chronic anemia, regular blood transfusions, and a high risk of iron overload. The global prevalence of beta thalassemia major continues to increase, including in Indonesia and the Lampung region. Excess iron is primarily stored as ferritin, which becomes toxic to hepatic tissue at high levels and is reflected by increased alanine transaminase (ALT) levels. This study aimed to analyze the relationship between ferritin and ALT levels in patients with beta thalassemia major through a literature review approach. Relevant scientific publications from reputable databases and accredited national journals were reviewed, focusing on studies that evaluated the association between these two parameters. The results demonstrated a statistically significant positive correlation (p < 0.05), in which elevated ferritin levels were consistently associated with increased ALT levels. These findings indicate a close relationship between iron overload and hepatocellular damage. However, the interpretation of ferritin and ALT levels should consider confounding factors such as inflammation, infection, and other clinical conditions that may influence laboratory results. Pathophysiologically, repeated blood transfusions lead to excessive iron accumulation that exceeds storage capacity, triggering oxidative stress, hepatocyte injury, and subsequent ALT release into circulation. Therefore, regular monitoring of ferritin and ALT levels is essential for early detection and prevention of hepatic complications in patients with beta thalassemia major.